2021
DOI: 10.2147/opth.s342593
|View full text |Cite
|
Sign up to set email alerts
|

Use of Amniotic Membrane in MMC-Augmented Trabeculectomy: A Retrospective Comparative Study

Abstract: Purpose: Amniotic membrane transplantation (AMT) has shown promising results as an antifibrotic agent in trabeculectomy. We aimed to evaluate the additional effect of AMT in MMC-augmented trabeculectomy. Patients and Methods: This retrospective study analyzed the results of the first 12 postoperative months of glaucomatous eyes submitted to Moorfields Safer Surgery Trabeculectomy with MMC alone (non-AMT group) compared to MMC and AMT (AMT group). Both groups were compared in terms of intraocular pressure (IOP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The available modalities for management included a combination of scleral fixation of PCIOL with augmented trabeculectomy or GDD. Augmentation of trabeculectomy with mitomycin-C or amniotic membrane has been shown to increase the success rates in refractory glaucoma 7 8. Sachdev et al in a retrospective study of 22 eyes on the scleral fixated intraocular lens with Ahmed tube surgery, reported good success in terms of IOP control and vision preservation in 29.0±19.4 months follow-up 2.…”
Section: Discussionmentioning
confidence: 99%
“…The available modalities for management included a combination of scleral fixation of PCIOL with augmented trabeculectomy or GDD. Augmentation of trabeculectomy with mitomycin-C or amniotic membrane has been shown to increase the success rates in refractory glaucoma 7 8. Sachdev et al in a retrospective study of 22 eyes on the scleral fixated intraocular lens with Ahmed tube surgery, reported good success in terms of IOP control and vision preservation in 29.0±19.4 months follow-up 2.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Roque et al presented a retrospective study of 51 eyes of 45 glaucoma patients, which compared trabeculectomy with mitomycin-c application to patients who had undergone trabeculectomy with mitomycin-c and amniotic membrane. This study showed no significant difference between the two groups, however, it should be noted that this was not a randomised and controlled cohort of patients due to the retrospective nature of the study [ 52 ].…”
Section: Glaucomamentioning
confidence: 98%
“…A 2015 Cochrane Review found 18 studies investigating the use of AMT with trabeculectomy. The review noted the data as low-quality but concluded that AMT can improve IOP slightly and may lead to fewer complications [ 181 ]. A systematic review of five RCTs showed that mean IOP was lower and that complications, including a flat anterior chamber and hyphema, were decreased in trabeculectomy with AMT compared to trabeculectomy without AMT [ 182 ].…”
Section: Strategies To Prevent Ocular Fibrosis Following Glaucoma Fil...mentioning
confidence: 99%